The Application of Polybara Media in Overcoming Arabic Reading Difficulties for Grade 7 Students at Mts 6 Boyolali - katon Katon; Nurul Latifatul Inayati Nurul (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
Teachers should be a master and understand of learning activity and also in using teaching media so that learning objectives can be successful and effective, as well as in selecting media as learning tools. One way to overcome this situation is to choose and use appropriate and good media in the learning process. Besides that, the large number of MTSn 6 Boyolali students who are not yet able to read Arabic is a factor in the lack of effective learning in class. Apart from that, the lack of media and facilities that support students in learning Arabic includes the lack of competence of Arabic language teachers. because this makes students unable to understand and memorize the Arabic language lessons given by the teacher. This requires teachers to be creative in using media that is interesting and easy to understand as well as helping students who are not yet able to read Arabic to be able to read Arabic, one of which is using "polybara" media so they can follow lessons in class. In this way, student learning outcomes will increase and achieve school education goals.